Contribution to a better understanding of flight pattern and egg-laying duration of the Pistachio seed wasp - Braham M. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
In Tunisia, the pistachio seed wasp, Eurytoma plotnikovi Nikolskaya (Hymenoptera, Eurytomidae) is a pest of economic importance attacking the edible part of the pistachio nut. The damage can be important seriously affecting harvest. To control the insect, a better knowledge of its biological features is needed. This paper aims to contribute to the understanding of adult flight activity, its extent and the duration of egg-laying period in order to establish better control methods. In the field, the emergence of adults from infested pistachio nuts of the previous year was monitored as was the progress of the development of diapausing larvae through pupae and adults by collecting and splitting old nuts at regular intervals from April to June in 2005, 2006 and 2011. The characterization of the egg-laying period was evaluated from April to July in 2005, 2006 and 2011 by sampling freshly nuts and dissecting. Results show that in 2005, the period of egg-laying was positioned between May 4 and June 4; in 2006, this period was concentrated in May and in 2011 between 7 May and 31 May. The splitting of aged nuts revels that in 2005, pupation started from the third decade of April with a presence of pupae inside aged nuts on April 27. Adult emergence began on May, 10 and ended by the end of month. In 2006, pupae were present in old nuts from April 18, the adults inside old nuts from May 26. Old larvae were detected in the nuts on June 28. With regard to 2011, overwintering larvae pupate in late April while adults begin their emergence from May 7, 2011. The results of this study will better positioning control operations against this pest.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)